Strategies for declining businesses - Harrigan, Kathryn Rudie (Toronto. : Lexington Books, 1980)
The author study of strategies for declining businesses goes far toward remedying this deficiency in the literature of business analysis.This book deals with an area of business management heretofore neglected. Her analysis is guided by two key hypothesis. First, the environmental features of declining industries differ. Second, even when environmental factors are held constant, there may be no unique strategy for effectively dealing with a declining industry; that is, several business strategies might be appropriate for dealing with declining demand in a given industry environment.
Includes index.
Includes bibliographical references p. 407-418 and index.
hza 31/07/2018
Loans
Keywords: Industrial management; Industries; United States